1999
DOI: 10.1177/00912709922008380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Endothelin‐Receptor Antagonist Bosentan on the Pharmacokinetics and Pharmacodynamics of Warfarin

Abstract: To investigate the effects of bosentan (Ro 47-0203), an endothelin receptor antagonist, on the pharmacokinetics and pharmacodynamics of warfarin, a double-blind, placebo-controlled, randomized, two-way crossover study was performed in 12 healthy male volunteers. All subjects received a single oral dose of 26 mg racemic warfarin twice, once in the morning of the 6th day of treatment with 500 mg bosentan twice daily for 10 days and once at the same time point during treatment with placebo twice daily for 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 17 publications
1
41
2
3
Order By: Relevance
“…Nonetheless, warfarin is a drug with a narrow therapeutic index, so that even slight changes must be considered in the context of clinical relevance. Drug interactions with warfarin have been previously demonstrated for the ERAs bosentan and sitaxsentan [9,[14][15][16]. These interactions have been attributed to alter-ations in the activity of CYP2C9 and CYP3A4 for bosentan and CYP2C9 for sitaxsentan, and these two enzymes are also primarily responsible for metabolism of warfarin.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, warfarin is a drug with a narrow therapeutic index, so that even slight changes must be considered in the context of clinical relevance. Drug interactions with warfarin have been previously demonstrated for the ERAs bosentan and sitaxsentan [9,[14][15][16]. These interactions have been attributed to alter-ations in the activity of CYP2C9 and CYP3A4 for bosentan and CYP2C9 for sitaxsentan, and these two enzymes are also primarily responsible for metabolism of warfarin.…”
Section: Discussionmentioning
confidence: 97%
“…Anaemia was not a problem in the present study population. Anticoagulation with the oral anticoagulant phenprocoumon was altered in the majority of patients, probably due to the induction by bosentan of cytochrome P 450 -dependent metabolism [26,27]. Thus close monitoring of the INR is indispensable in patients undergoing anticoagulation therapy with phenprocoumon as long as they receive bosentan.…”
Section: Discussionmentioning
confidence: 99%
“…Glyburide and cyclosporine A are contraindicated with concurrent bosentan therapy. Although a small study has shown that humans given bosentan 500 mg twice daily have reduced warfarin effect (35), no influence on warfarin activity has been seen in the clinical trials using the 125-mg and 250-mg twice-daily doses of bosentan.…”
Section: Safetymentioning
confidence: 99%